Use of standard musculoskeletal ultrasound to determine the need for fasciotomy in an elevated muscle compartment pressure cadaver leg model. Issue 3 (March 2019) - Marmor, Meir; Charlu, Jonathan; Knox, Riley; Curtis, William; Hoogervorst, Paul; Herfat, Safa
Highlights: Readily available ultrasound technology can be used to detect elevated muscle compartment pressures. Pressure used to generate deformity (flattening) of the fascial planes, in comparison to the uninvolved extremity, may be the best index to use. The manuscript demonstrates proof of concept on the anterior leg compartment that needs to be validated on other compartments and clinically. Abstract: Introduction: Acute compartment syndrome (ACS) is a limb-threatening condition often associated with leg injury. The only treatment of ACS is fasciotomy with the purpose of reducing muscle compartment pressures (MCP). Patient discomfort and low reliability of invasive MCP measurements, has led to the search for alternative methods. Our goal was to test the feasibility of using ultrasound to diagnose elevated MCP. Methods: A cadaver model of elevated MCPs was used in 6 cadaver legs. An ultrasound transducer was combined with a pressure sensing transducer to obtain a B-mode image of the anterior compartment, while controlling the amount of pressure applied to the skin. MCP was increased from 0 to 75 mmHg. The width of the anterior compartment (CW) and the pressure needed to flatten the bulging superficial compartment fascia (CFFP) were measured. Results: Both the CW and CFFP showed high correlations to MCP in the individual cadavers. Average CW and CFFP significantly increased between baseline and the first elevated MCP states. Both Inter-observer and intra-observer agreements for the ultrasound measurements were good to excellent. Discussion: Ultrasound indexes showed excellent correlations in compartment pressures, suggesting that there is a potential for the clinical use of this modality in the future.